Предмет: Алгебра,
автор: Mmila44
Раскрой скобки и упрости выражение.
−(11x+6,1y)−(−13y−3,1x)
Ответы
Автор ответа:
1
Ответ:
−(11x+6,1y)−(−13y−3,1x)= -11x-6,1y+13y+3,1x= -7,9x+6,9y
Автор ответа:
1
Ответ:
-7,9x+6,9y
Объяснение:
−(11x+6,1y)−(−13y−3,1x)=-11x-6,1y+13y+3,1x=-7,9x+6,9y
Mmila44:
спасибо
Похожие вопросы
Предмет: Другие предметы,
автор: litalis
Предмет: Қазақ тiлi,
автор: мишашарабарин
Предмет: Русский язык,
автор: fosteman
Предмет: Математика,
автор: 1234766
Предмет: Математика,
автор: арина10102006